Preparation and evaluation of conjugate nanogels of glycyl-prednisolone with natural anionic polysaccharides as anti-arthritic delivery systems - Kohei Mizuno; Yuri Ikeuchi-Takahashi; Yoshiyuki Hattori; Hiraku Onishi (Taylor & Francis Group, 2021)
Although prednisolone (PD) is used as an anti-arthritis drug due to its rapid and strong anti-inflammatory potential, its frequent and large dosing often brings about adverse effects. Therefore, targeting therapy has attracted increasing attention to overcome such adverse effects. In the present study, nanogels (NGs) composed of macromolecule-PD conjugates were developed as a novel targeting delivery system, and their anti-inflammatory potential was examined. Conjugates were prepared by carbodiimide coupling between glycyl-prednisolone (GP) and the natural anionic polysaccharides, alginic acid (AL) and hyaluronic acid (HA). NGs were produced by the evaporation of organic solvent from the conjugate solution. The obtained NGs, named AL-GP-NG and HA-GP-NG, respectively, were examined for particle characteristics, in vitro release, pharmacokinetics, and in vivo efficacy. Both NGs were several hundred nanometers in size, had negative zeta potentials, and several % (w/w) drug contents. They released PD gradually at pH 7.4 and 6. They exhibited fairly good retention in the systemic circulation. In the efficacy examination using rats with adjuvant-induced arthritis, both NGs showed the stronger and more prolonged suppression of paw inflammation than PD alone. These suggested that the present NGs should be possibly useful as anti-arthritis targeting therapeutic systems.